2018
DOI: 10.1021/acs.jproteome.8b00127
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Quantitative LC-MS/MS Analysis of N-linked Glycans Derived from Glycoproteins Using Sodium Deoxycholate Detergent

Abstract: Protein glycosylation is a common protein post-translational modification (PTM) in living organisms and has been shown to associate with multiple diseases, and thus may potentially be a biomarker of such diseases. Efficient protein/glycoprotein extraction is a crucial step in the preparation of N-glycans derived from glycoproteins prior to LC-MS analysis. Convenient, efficient and unbiased sample preparation protocols are needed. Herein, we evaluated the use of sodium deoxycholate (SDC) acidic labile detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…A significant amount of protein loss happens when proteins are recovered from the spin filter membranes. Several studies have been done utilizing SDC during gel or in‐solution digestion sample preparations [21–26]. Besides, the application of SDC to plasma proteomics sample preparations was done successfully [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of protein loss happens when proteins are recovered from the spin filter membranes. Several studies have been done utilizing SDC during gel or in‐solution digestion sample preparations [21–26]. Besides, the application of SDC to plasma proteomics sample preparations was done successfully [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…MWCO filters were found to selectively bind certain glycans, and a detergent wash step (sodium deoxycholate, SDC) was added to the method (MWCO-SDC-IPC), which has been shown to be an improvement in filter-aided sample preparation in protein and glycoprotein digestion. 39,40 In addition, we used the PA-IPC method, which reliably identifies, quantifies and recovers more glycans, to compare the glycan profiles of innovator Herceptin® antibody products (6 lots, HER1 to HER6; 4 European and 2 US) with internal developmental biosimilar drug substance (scale-up bioreactor runs).…”
Section: Introductionmentioning
confidence: 99%
“…and Zhu et al. . In case of the former , cell lysate was transferred into the filter membrane, and sodium dodecyl sulfate (SDS) was used as a detergent.…”
Section: Advances In Glycan Release Techniquesmentioning
confidence: 99%
“…N‐ glycan profiles of wild‐type and mutant Chinese hamster ovary cell lysates suggested that this method referred to as filter‐aided‐ N‐ glycan separation (FANGS) is not biased to any N‐ glycan . More recently, Mechref and coworkers compared PNGase F digestion efficiency with and without sodium deoxycholate (SDC) . SDC is a detergent that was first introduced in proteomics studies to enhance protein solubilization, allowing the easy removal of the detergent by acid precipitation before MS analysis.…”
Section: Advances In Glycan Release Techniquesmentioning
confidence: 99%
See 1 more Smart Citation